Digitalisasi UMKM: Pendayagunaan Media Sosial sebagai Sarana Pemasaran - Elisa Rahmawati; Sri Yuliani; Dherisa Novinda Sari; Fanny Damara Afifah; M. Gilang Narasrestha Candraditya Cipta; Nayla Andina Kamiliya; Taskur Ajam Aji; Yuliana Diyah Novitasari; Daffarzha Adam Habiel ‘Nur (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
In the current era, the development of MSMEs in the utilization of natural resources continues to be carried out in order to support the family economy. However, in reality, there are still problems in developing MSME, namely the lack of understanding and knowledge of MSME actors related to agricultural product innovation and the use of digitization so that the sale of agricultural products is still at standard prices and not widely known. The purpose of this community service is to help change the people's mindset in selling agricultural products and utilizing social media as a sales strategy in order to increase selling prices and expand the market so as to support the family economy and reduce poverty. The approach used is a participatory approach by involving the community in the process. Partners in this community service are MSME actors in Sambiharjo Village, Paranggupito District, Wonogiri. The results of this community service activity are in the form of giving directions regarding product packaging and product marketing with digitization efforts. Product innovations produced by MSME actors should be maintained and followed up so that they can be effective in supporting MSME development and increasing product selling prices and supporting the family economy.